α-synuclein and tau: interactions, cross-seeding, and the redefinition of synucleinopathies as complex proteinopathies - Padilla-Godínez, Francisco J.; Vázquez-García, Eunice Ruth; Trujillo-Villagrán, María Isabel; Soto-Rojas, Luis O.; Palomero-Rivero, Marcela; Hernández-González, Omar; Pérez-Eugenio, Francisco; Collazo-Navarrete, Omar; Arias-Carrión, Oscar; Guerra-Crespo, Magdalena (Frontiers in Neuroscience, 2025)
Neurodegenerative diseases are characterized by protein aggregation and overlapping pathologies, challenging traditional classifications and highlighting shared underlying mechanisms. Parkinson’s disease and related synucleinopathies, including Lewy body dementia and multiple system atrophy, highlight the interplay between α-synuclein and tau, two key proteins implicated in these disorders. Recent studies reveal that tau and α-synuclein co-aggregate, interact synergistically, and propagate via prion-like mechanisms, exacerbating neuronal dysfunction. This review examines the physiological roles and pathological transitions of tau and α-synuclein, emphasizing their roles in microtubule dynamics, synaptic regulation, and the structural heterogeneity of aggregates. Evidence from post-mortem brains, transgenic models, and proteomic analyses underscores the significance of soluble oligomers as primary neurotoxic species and explores the diverse molecular composition of Lewy bodies and glial cytoplasmic inclusions. The co-localization of tau and α-synuclein, influenced by genetic factors and post-translational modifications, offers insights into shared mechanisms across synucleinopathies and tauopathies. These findings advocate for integrated therapeutic strategies targeting protein cross-seeding and proteostatic disruption while preserving physiological roles. By framing neurodegeneration as a collapse of proteostatic networks rather than isolated proteinopathies, this work proposes a paradigm shift toward understanding and treating complex neurodegenerative disorders.